유튜브 온라인 동영상 광고 트렌드 분석 - 이운형; Woon-hyung Lee (한국디자인포럼, 2016)
연구배경 유튜브를 비롯한 영상 콘텐츠 시장은 폭발적인 성장세를 보이고 있으며, 이에 따라 동영상 콘텐츠로 활용되는 바이럴 영상광고와 시청 중 나타나는 인스트림 광고 등 온라인 동영상 광고가 활발하게 제작되고 있다. 유튜브에서의 온라인 영상광고는 영상광고의 특징뿐만 아니라 인터넷 광고의 특성도 가지고 있어 기존의 TV광고의 제작과는 다른 방식으로 접근해야 할 필요성이 있으며, 따라서 기존의 영상 매체를 이용한 광고와는 다른 형태의 크리에이티브에 관한 연구의 필요성이 제기된다. 연구방법 본 연구에서는 유튜브 온라인 동영상 광고의 크리에이티브 특성에 관해 고찰하며, 최근 유튜브에서 활용되고 있는 광고들을 분석하여 현재 트렌드에 대해 종합적으로 이해하고 이를 통해 향후 온라인 동영상 광고 제작에 본 연구의 결과가 유용하게 활용될 수 있도록 하는 것을 그 목표로 한다. 연구결과 유튜브에서의 영상광고 형태는 바이럴 영상광고와 인스트림 광고 형태의 두 가지로 나눌 수 있었다. 광고 크리에이티브 측면에서 성공적인 유튜브 광고영상들의 경우 시청자들의 주목을 끌고 광고 회피 현상을 최소화하기 위해 유머러스한 내용과 영상을 많이 채택하고 있었으며, 이는 시청자들 사이에 공유를 통해 광고 효과를 누리는 결과로 이어지게 되는 것으로 분석되었다. 결론 유튜브 온라인 동영상 광고의 경우 효과적인 광고 목표의 달성을 위해 감성적이면서도 재미있는 메시지를 통한 소비자들의 설득과 함께 광고회피 현상을 최소화시킬 수 있는 효과적인 크리에이티브 전략이 요구된다 하겠다. Background Content market including Youtube is being exploded, thus online video advertising such as viral and in-stream advertising is being produced actively. Online video advertising has the characteristics of the internet advertising as well as video advertising. Therefore it should be approached by the different method compared to TV advertising. Therefore, the research about its creative is needed, different to legacy advertising. Methods In this paper, the characteristics of creative will be examined and recent Youtube advertising will be analyzed. the purpose of this paper is to understand the trend of online video advertising and use the result in the field of advertising. Result in the result of analysis, the form of online video advertising on Youtube is mainly the form of video content. It can be divided into two types, first one is the viral video advertising which targets the effect of viral marketing and second one is in-stream advertising which is played before playing the main video content. On the side of creative, successful advertising used humorous contents and images in order to get the audiences` attention. Conclusion In the case of Youtube online video advertising, effective creative strategy is needed to minimize the avoiding advertising and persuade consumers through emotional and fun message.